Maternal investment affects offspring phenotypic plasticity in a viviparous cockroach - Holbrook, Glenn L. (National Academy of Sciences, 2004)
Maternal effects, crossgenerational influences of the mother's phenotype on phenotypic variation in offspring, can profoundly influence the fitness of offspring. In insects especially, social interactions during larval development also can alter life-history traits. To date, however, no experimental design, to our knowledge, has manipulated the prenatal and postnatal environments independently to investigate their interaction. We report here that the degree of maternal nutrient investment in developing embryos of the viviparous cockroach Diploptera punctata influences how quickly neonate males become adults and how large they are at adulthood. An offspring's probability of reaching adulthood in fewer than four molts increased with birth weight: the heavier neonates were, consequently, more likely to become smaller adults. Social interaction also affected nymphal development and adult size. Nymphs reared in pairs molted fewer times than solitary nymphs and, thus, became smaller adults. The social effect on developmental trajectory was, however, eliminated by experimentally increasing the level of maternal nutrient investment per offspring, which was accomplished by removing one of the female's paired ovaries (allometric engineering). We conclude that a particular prenatal environment can result in different offspring phenotypes under different postnatal social conditions. By investing more in each offspring, however, D. punctata mothers, because they are viviparous, are able to produce broods with environmentally (socially) independent phenotypes.